2016
DOI: 10.1111/evj.12560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal dexamethasone treatment on pancreatic β cell function in the pregnant mare and post natal foal

Abstract: Dexamethasone administration induced changes in maternal insulin-glucose dynamics, indicative of insulin resistance and had subtle longer term effects on post natal β cell function of the foals. The programming effects of dexamethasone in horses may be mediated partially by altered maternal metabolism and placental growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…Much of what 232:1 we know about glucocorticoid induced programming of disease is based on animal studies using synthetic glucocorticoids such as dexamethasone. Numerous studies have demonstrated that maternal exposure to dexamethasone can reduce foetal or postnatal growth and impair offspring cardiometabolic physiology (Langdown et al 2001, de Vries et al 2007, Quinn et al 2014, Valenzuela et al 2016. Importantly, this growth restriction is often associated with compensatory catch-up growth, which may further increase the risk of cardiometabolic outcomes (Ozanne 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Much of what 232:1 we know about glucocorticoid induced programming of disease is based on animal studies using synthetic glucocorticoids such as dexamethasone. Numerous studies have demonstrated that maternal exposure to dexamethasone can reduce foetal or postnatal growth and impair offspring cardiometabolic physiology (Langdown et al 2001, de Vries et al 2007, Quinn et al 2014, Valenzuela et al 2016. Importantly, this growth restriction is often associated with compensatory catch-up growth, which may further increase the risk of cardiometabolic outcomes (Ozanne 2001).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Similarly, dexamethasone treatment of mares during late pregnancy alters arginine-stimulated insulin secretion in their foals 12 weeks after birth relative to controls of the same BW. 20 Collectively, the experimental and epidemiological studies have led to the concept that postnatal metabolic phenotype can be programmed in utero, particularly by environmental conditions suboptimal for normal fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…In the fetal sheep (Fowden 1980, Aldoretta et al 1998 and horse (Fowden et al 1980(Fowden et al , 1982(Fowden et al , 2005, and also in atricial species such as the rat (Kervran et al 1979, Kervran & Randon 1980, there are maturational changes in pancreatic function in late gestation with increasing insulin secretion in response to glucose and arginine stimulation. These changes are associated with increasing endogenous cortisol concentrations in the prepartum period (Fowden et al 2005), can be modified by exogenous stimuli such as maternal undernutrition (Oliver et al 2001), multiple conception (Rumball et al 2008, Green et al 2011 and exogenous glucocorticoid administration (Valenzuela et al 2017) and extend into postnatal life. It has also been reported that there is a wave of β-cell apoptosis in late gestation in the human (Tornehave & Larsson 1997), which may represent a change from fetal β-cells to more mature β-cells in preparation for extra-uterine life.…”
Section: How Might Preterm Birth Be Linked With Later Diabetes?mentioning
confidence: 99%